2011
DOI: 10.1111/j.1600-0412.2010.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and postoperative recovery in fast‐track hysterectomy

Abstract: Objective: To determine whether health-related quality of life (HRQoL) and postoperative recovery of women who undergo abdominal hysterectomy in a fast track program under general anesthesia (GA) differ from women who receive spinal anesthesia with intrathecal morphine (SA).Design: Secondary analysis from an open randomized controlled multicentre study.Setting: Five hospitals in south east Sweden.Population: 180 women admitted for abdominal hysterectomy for benign disease were randomized; 162 completed the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
2
31
0
3
Order By: Relevance
“…Implementation of an enhanced recovery pathway at our institution readied patients for a discharge on POD 1, which is earlier than other studies of gynecological patients. [16][17][18][19] Studies of enhanced recovery in gynecology have focused on laparoscopic surgery or featured a mix of benign and malignant surgical indications. 15,16 We describe a pathway oriented specifically at an open surgical approach for treating benign disease that allows practitioners to identify patients appropriate for HER pathway application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of an enhanced recovery pathway at our institution readied patients for a discharge on POD 1, which is earlier than other studies of gynecological patients. [16][17][18][19] Studies of enhanced recovery in gynecology have focused on laparoscopic surgery or featured a mix of benign and malignant surgical indications. 15,16 We describe a pathway oriented specifically at an open surgical approach for treating benign disease that allows practitioners to identify patients appropriate for HER pathway application.…”
Section: Discussionmentioning
confidence: 99%
“…17 To guide the development of our pathway, we performed a structured review of the literature using PubMed, Google Scholar, and Embase databases to identify evidence-based interventions associated with improved pain control and functional recovery, decreased nausea and vomiting, or decreased LOS after gynecologic surgery. Our review revealed that: 1) spinal anesthesia, in comparison with general anesthesia, is associated with shorter sick leaves 18 and improved quality of recovery and of life scores; 19 2) compared with general anesthesia, spinal anesthesia with intrathecal morphine reduces postoperative pain, ileus, fatigue, hospital LOS, and nausea and vomiting for up to 24 hr postoperatively; 20,21 3) transversus abdominis plane (TAP) blocks are associated with improved postoperative pain control and reduced rates of nausea and vomiting; 22 4) foundational multi-modal analgesia achieves postoperative pain control effectively and efficiently. 23,24 Hysterectomy enhanced recovery pathway Review of the literature, in combination with clinical expertise of the multi-disciplinary team was used to create the hysterectomy enhanced recovery (HER) pathway.…”
Section: Résumémentioning
confidence: 99%
“…Side effects of spinal anaesthetic were, however also clearly demonstrated with increases in vomiting and pruritis after spinal anaesthetic. (Wodlin, 2011b(Wodlin, , 2011c(Wodlin, , 2011d The second trial looking at mode of anaesthesia, by Kroon et al (2010), compared different anaesthetic methods (PCA and volatile anaesthesia vs. intrathecally administered morphine and TIVA) in 53 randomised patients undergoing abdominal hysterectomy for benign indications. It was noted that most of the uteri in the study were oversized as normal practice in the unit in question was to opt for vaginal hysterectomy for normal-sized uteri.…”
Section: Discussionmentioning
confidence: 99%
“…(Wodlin, 2011a, 2011b, 2011c, Kroon, 2010 The work by the 'GASPI' study group was a multicentre randomised controlled trial involving a total of 162 women undergoing total or subtotal hysterectomy for benign indications. The patients were relatively fit: contraindications to participation in the trial included an ASA score of ≥3, gynaecological malignancy and physical or psychiatric disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation